Unveiling the Gut Mysteries of Enteric Duplication Cysts: A Case Series of Nine Cases - Jaydeep N. Pol; Priya N. Hombalkar; Anand A. Bhosale; Rashmi G. Sawant; Vivek J. Dugad; Ajay L. Sabnis (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Enteric duplication cysts are rare, having an incidence of one in 4500 births. Due to nonspecific symptoms and variations in location and size, the clinical diagnosis is difficult. Delayed diagnosis can cause serious complications leading to morbidity and mortality. Methods: This case series comprises nine cases retrieved from February 2014 to January 2024, and includes a rare adult case of an enteric duplication cyst. Data were collected, tabulated, and analyzed by descriptive statistics using Microsoft Excel 2016. Results: The male: female ratio was 2:1. A wide age range was encountered (8 days to 50 years with a median of 2 years). The most common site of enteric duplication cyst was ileum (6/9, 66.7%). On histopathological examination, the cysts ranged in size from 2 cm to 15.7 cm (mean: 7.05 ± 4.7 cm). Maximum cases were cystic in appearance (7/9, 77.8%). One unique adult case showed complications of fibrous adhesions (1/9, 11.1%). Multiplicity of duplication cysts was observed in (2/9, 22.2%) cases. Heterotopic mucosa was noted in (2/9, 22.2%) cases, of which one case showed gastric mucosa in a double cyst setting in the jejunum and another case showed concurrent gastric and pancreatic mucosa in the ileum. Associated anomalies like Meckel’s diverticulum and neurogenic cyst were noted in (2/9, 22.2%) cases. Conclusion: Although rare, the consideration of duplication cysts is crucial when evaluating patients with acute abdomen, especially in neonates and children. Ultrasound examination is the investigation of choice exhibiting classic gut sign positive. Early detection through timely diagnosis and surgical intervention holds the key to preventing adverse outcomes.